Analysis of determinants of the inflow of foreign direct investment to Poland. Part II – research results - Wyrwa Joanna (Management, 2020)
This study contains an analysis of the main determinants of the inflow of foreign direct investment to Poland. This article is devoted to the analysis of the main motives determining the inflow of foreign direct investment to Poland. It is the second part of the series and presents the scale and dynamics of FDI inflow to Poland between 2010 and 2018, as well as the results of own research carried out using structural equation modeling. This study focused on determining the cause-and-effect relationship between the scale of inflow of foreign direct investment and selected macroeconomic parameters of the economy. Based on the theories and results from previous research, a model was developed in which the variables and the nature of their relationship were determined. The model is based on four latent exogenous variables describing FDI determinants and one latent endogenous variable describing FDI inflow. In the article, structural equation modeling was indicated as a method for analyzing the factors conditioning the inflow of foreign direct investment. The proposed research concept will allow supplementing and extending the analysis of FDI determinants in Poland.